A First Case Report of Talaromyces Marneffei Infection Presenting as a Nonresolving Pneumonia in a Non-hiv Diabetic Patient From Bangladesh - Haque, Hasna Fahmima; Ahmed, AKM Shaheen; Hoque, Tariful; Saha, Repon Chandra; Afroz, Farhana (Bangladesh Journal of Medicine, 2022)
Talaromycosis is a systemic fungal infection caused by dimorphic fungus Talaromyces marneffei. It is endemic in Southeast Asia and generally complicates immunocompromised individuals, especially those infected by human immunodeficiency virus (HIV). Here, we report an autocthonus case of talaromycosis occurring in a non-HIV-infected Bangladeshi type 2 diabetic patient who presented with non-resolving pneumonia. To the best of our knowledge, this is the first talaromycosis case being reported from Bangladesh. Bangladesh J Medicine 2022; 33: 62-64